Analisis Hukum Proses Pergantian Antar Waktu (PAW) Anggota DPRD Kabupaten Empat Lawang Terkait Pelanggaran AD/ART Partai Politik - Reza, Mehmed; Salia, Erli; Saptawan, Ardiyan; Mahfuz, Abdul Latif (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this paper is that Time Between Time Switching (PAW) is a mechanism in the representative system to replace board members who resign, die, or are dismissed. This research focuses on legal analysis of the PAW process of members of the Four Lawang Regency DPRD who are involved in violations of the Articles of Association / Bylaws (AD / ART) of political parties. The method used is normative legal research with a statutory and case approach. The results showed that the PAW process due to violations of political parties' AD/ART refers to applicable regulations but often causes controversy. This is due to the vagueness of the definition of